2016
DOI: 10.3390/en9070516
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Gas: Experimental Study of the Influence of Subcritical Carbon Dioxide on the Mechanical Properties of Black Shale

Abstract: An experimental study was performed to investigate the effect of subcritical carbon dioxide (CO 2 ) adsorption on mechanical properties of shales with different coring directions. Uniaxial compressive strength (UCS) tests were conducted on shale samples with different CO 2 adsorption time at a pressure of 7 MPa and a temperature of 40˝C. The crack propagation and the failure mechanism of shale samples were recorded by using acoustic emission (AE) sensors together with ARAMIS technology. According to the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Strength may remain constant because of the precipitation of secondary carbonate minerals, which counterbalances calcite dissolution. In contrast, for black shales exposed to gaseous and scCO 2 –water mixtures for various time periods, gradual decreases in the uniaxial compressive strength, Young's modulus, and the brittleness index were observed with increasing exposure time, and the impact was greater for the scCO 2 –water case …”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Strength may remain constant because of the precipitation of secondary carbonate minerals, which counterbalances calcite dissolution. In contrast, for black shales exposed to gaseous and scCO 2 –water mixtures for various time periods, gradual decreases in the uniaxial compressive strength, Young's modulus, and the brittleness index were observed with increasing exposure time, and the impact was greater for the scCO 2 –water case …”
Section: Alteration Of Mechanical Propertiesmentioning
confidence: 85%
“…In contrast, for black shales exposed to gaseous and scCO 2 -water mixtures for various time periods, gradual decreases in the uniaxial compressive strength, Young's modulus, and the brittleness index were observed with increasing exposure time, and the impact was greater for the scCO 2 -water case. 163,164 The fluid chemistry plays a major role in the mechanical response, as shown by Rathnaweera et al 159 They investigated the mechanical response of a quartz-rich sandstone as saturating fluids (water, CO 2 , brine, and brine-saturated CO 2 ) with varying compositions that were used to induce geochemical reactions. The nature of the saturating fluid influenced the strength, the Young's modulus, and the failure mode.…”
Section: Static Tests On Reservoir Rock In Gcs Conditionsmentioning
confidence: 99%
“…In recent years, SC-CO 2 fluid, which has many advantages for improving the rates of penetration and single well recovery, has been applied in the field of drilling and completion engineering, especially for the exploitation of unconventional reservoirs [7][8][9][10]. Moreover, it is reported that a SC-CO 2 jet has better rock erosion and fracturing capacity than a water jet does, thus, it has been widely considered as a promising and novel jet technology [11][12][13][14]. Besides, inside a reservoir bed, the dissolution of organic deposition by the seepage of SC-CO 2 can increase the permeability of the reservoirs, and the absorbed natural gas can be displaced through competitive adsorption with SC-CO 2 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing body of research on the rock breaking of the SC-CO 2 jet, there are no descriptions of the mechanical or thermodynamic properties of the rock. The mechanical and thermodynamic properties of cement rock, sandstone, shale, and marble were investigated, [37][38][39][40][41][42][43] as shown in Table 2. It can be seen that the variation in the same kind of rock is great.…”
Section: Governing Equations Of Rock Mechanics and Rock Mechanical Anmentioning
confidence: 99%